Our Skynet Moment: Debating Morality of AI - Jayakumar, Shashi (2016)
The rapid growth of artificial intelligence (AI) has serious implications for our future. The issues and their oversight are not just the domain of computer engineers, technologists and AI experts. Policymakers, Smart Nation experts and security officials too should come together with them to ponder implications and set out the parameters, if needed, for future research and development.